EIKODEKANA DARI DAUN TUMBUHAN GEDI (ABELMOSCHUS MANIHOT L. MEDIK) ASAL SULAWESI UTARA - Mamahit, Lexie (Sam Ratulangi University, 2009)
This research was aimed to isolate and identify the structure of secondary metabolities from gedileaf. In order to achieve this research aim, an extraction of the gedi leaf tissue with mwthanol solvent hadbeen carried out. These extract then was partitioned in several organic solvents such as n-hexane,chloroform, and ethyl acetate. Further, the resulted partition was fractionation and purifying undergoes anappropriate method like liquid and vacuum pressure chromatography. To determine the chemical structureof the isolate, a complication of several spectroscopic methods, such as infrared (IR), 1H and 13 C nuclearmagnetic resonance (NMR), and an advanced NMR techniques (HMQC, HMBC, and COSY). Results ofthis research shown that one major constituent was isolated from the leaf of gedi: eikodekana Keywords : eikodekana, Abelmoschus manihot